Economics of rainguarding: A comparative analysis - Joseph T; Cyriac J; Haridasan V (Indian Journal of Natural Rubber Research, 1989)
The comparative cost advantages of two types of rainguarding of rubber trees are analysed on the basis of a field survey. Using the survey data and secondary information, an investigation of the average yield which will justify rainguarding is also carried out through discounted cash flow analysis. the study found that the minimum average yield required for recommending rainguarding is 675 kg/ha.
Keywords: Benefit cost ratio; Cost of rainguarding; Discounted cash flow analysis; Polythene sheets; Rainguarding; Tapping shade